Integration of waste in SDGs - Puspita Nurlilasari; Devi Maulida Rahmah; Roni Kastaman (PT SOLUSI EDUKASI BERDIKARI, 2025)
The accelerating threats of climate change and environmental degradation require industries to adopt holistic and integrated solutions that go beyond conventional pollution control. This paper presents a comprehensive analysis of the integration between carbon credit systems and industrial wastewater management, viewed through the lens of chemical engineering and process optimization. It emphasizes how the synergistic deployment of carbon reduction technologies and wastewater treatment innovations can support global climate and water sustainability targets, particularly Sustainable Development Goals (SDGs) 6 (Clean Water and Sanitation), 7 (Affordable and Clean Energy), 9 (Industry, Innovation and Infrastructure), 12 (Responsible Consumption and Production), and 13 (Climate Action). By exploring both technological and policy frameworks—including the Paris Agreement, national emission regulations, and voluntary market mechanisms such as the Gold Standard and Verified Carbon Standard—this study outlines pathways for industries to reduce their greenhouse gas emissions while simultaneously improving water quality, recovering energy and nutrients, and enhancing economic returns through circular resource use. The paper also identifies key challenges in implementation, including verification complexity, regulatory gaps, and financial constraints, and proposes innovations such as modular bioelectrochemical systems, microalgae-based treatment for CO₂ fixation, and blockchain-enabled carbon credit verification. In doing so, it aims to provide a roadmap for climate-resilient and environmentally sound industrial transformation grounded in chemical engineering principles.